PENGEMBANGAN BAHAN AJAR ANIMASI KARIKATUR UNTUK KETERAMPILAN MENULIS TEKS ANEKDOT DI SMA - Husna, Nurul (Jurnal Lazuardi, 2025)
This animated caricature anecdote text teaching material is an anecdote text teaching material accompanied by animated caricature images. The purpose of developing this teaching material is to determine the development of students' writing skills so that students can relate the material and create anecdotal texts that are related to students' daily lives. This type of research uses the method used, namely Research and Development (R&D) developed by Branch with the ADDIE approach. This development model has five stages of development, including analysis, design, development, implementation, and evaluation. Data collection is carried out by searching for related references from various relevant sources and in accordance with the current independent curriculum, then determining the indicators to be achieved based on the flow of learning objectives (ATP) and learning outcomes (CP) in accordance with the learning materials used in the study. While the instrument used in data collection in this study is a questionnaire. This instrument was developed through product research looking at the learning aspects, material content, and media aspects. Based on the results of the data analysis, it was concluded that the new product resulting from the development was suitable for use because it was in the "Very Good" category and the level of product effectiveness on student understanding was in the "Capable" category.